Boxing - Ruddock, A.; Wilson, D.; Hembrough, D. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Successful performance in professional boxing is determined by a boxer`s ability to control the contest. This is achieved by demonstrating superior offensive, defensive and ringmanship skills. A professional boxer must therefore possess a variety of technical skills supported by a wide variety of physical attributes. A large aerobic capacity is required to support physiological demands imposed by training and competition and can be developed mainly through intelligent programming of sprint and high-intensity interval training. A forceful punch is integral to contest control and is dependent on the impulse momemtum relationship. Strength training to develop hip and knee extension maximum force and rate of force development coupled with the core musculature training to improve torque through the hips and upper body should be a key focus for a professional boxer. In addition, improving range of motion and developing mobility of the shoulders and hip musculature will help improve force transmission from the foot to the fist.